Liver Infarction in a Patient with HELLP and Probable Anti-phospholipid Syndrome - Cihan Kaya; Hüseyin Cengiz; Murat Ekin; Ammar Kanawati; Levent Yaşar (Gynecology Obstetrics & Reproductive Medicine)
The aim of this report is to make an awareness about hepatic infarction in those patients with progressively elevating liver enzymes and anti-phospholipid syndrome. A 29-year-old G2P2 woman who has undergone cesarian section (C-section) due to fetal distress was referred to our department with progressively elevating liver enzymes and lowering platelets. Computed tomography revealed a hepatic infarction with a dimension of 14x10 cm. Further, laboratory parameters defined an elevated Cardiolipin IgM antibody (11.59 U/ml). She had a diagnosis of HELLP and probable anti-phospholipid syndrome due to these findings. She did well with the administered anticoagulant and steroid therapy. Pregnant women with progressively elevating liver enzymes should be evaluated for hepatic infarction and underlying diseases such as anti-phospholipid syndrome.